Investigation of the structural changes of cocoa bean (with and without seed coat) during convective drying - Ndukwu, Macmanus Chinenye; Simonyan, K J; Ndirika, V I O (International Journal of Agricultural and Biological Engineering, 2012)
The influence of seed coat on the behaviour of heterogeneous structure of cocoa bean (frosteros sp.) during convective drying with tempering period was investigated in an isothermal condition. It was found that the removal rate of moisture and air diffusion between the cocoa kernel and seed coat is not the same especially at the temperature of 55